2017
DOI: 10.1111/vox.12489
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes and amotosalen/UVA‐treated platelet utilization in massively transfused patients

Abstract: Background Amotosalen/UVA-treated platelet concentrates (PCs) have demonstrated efficacy for treating and preventing bleeding in clinical trials and in routine use; however, most studies were performed in haematology/oncology patients. We investigated efficacy during massive transfusion (MT) in general hospitalized patients.Methods Universal amotosalen/UVA treatment (INTERCEPT Blood System) of platelets was introduced at a large Austrian medical centre. We performed a retrospective cohort analysis comparing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…Similarly, data on product usage per patient are necessary to document the efficacy of PR PLTs. Data addressing these points have been published by our group [37][38][39] and others [19][20][21][22][23][24][34][35][36]40 providing evidence supporting the concept that diminishing the infectious risk by crosslinking nucleic acids does not negatively impact PLT activation or hemostatic efficacy. Other studies, however, including the EFFIPAP trial have also addressed this issue.…”
Section: Ongoing Quality Monitoringmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, data on product usage per patient are necessary to document the efficacy of PR PLTs. Data addressing these points have been published by our group [37][38][39] and others [19][20][21][22][23][24][34][35][36]40 providing evidence supporting the concept that diminishing the infectious risk by crosslinking nucleic acids does not negatively impact PLT activation or hemostatic efficacy. Other studies, however, including the EFFIPAP trial have also addressed this issue.…”
Section: Ongoing Quality Monitoringmentioning
confidence: 98%
“…[14][15][16][17][18] Psoralen-based PR techniques have been utilized in Europe for many years, and multiple published studies support the benefits and safety of PR products. [19][20][21][22][23][24] Phase III clinical trials are also ongoing for riboflavin (MIPLATE) and UV-C light-based PR techniques for PLTs (CAPTURE). 4,25,26 PR systems are also currently available for plasma and cryoprecipitate.…”
Section: Role Of Psoralensmentioning
confidence: 99%
“…Plasma PRTs, which have been reviewed by Seltsam and M€ uller (2013), will not be discussed here, as plasma is infrequently required for the treatment of haematological transfusion recipients. Specific information and speculations on the use of blood components treated with PRTs in massive transfusion protocols and trauma resuscitation can be found in other recent publications (Hess et al, 2016;Mays & Hess, 2017;Arbaeen et al, 2017;Nussbaumer et al, 2017;Thomas et al, 2019).…”
Section: Current Risk Of Transfusion Transmissible Infections In Haemmentioning
confidence: 99%
“…Hemovigilance data demonstrate a low rate of adverse events with PR platelets, 12 and some studies fail to demonstrate increased bleeding or worse clinical outcomes for patients treated with PR platelets. 13,14 However, studies have shown an association between PR platelets and a reduction in 1-and 24-hour corrected count increments, increase in platelet refractoriness, decrease in time to next transfusion, and increase in platelet use. [15][16][17] The most recent study demonstrated a 50% increase in platelets transfused and a 25% increase in red blood cells transfused in patients receiving INTERCEPT vs control platelets.…”
Section: Clinical Efficacymentioning
confidence: 99%